Effect of Seed Pelleting with Microbial and Organic Filler Materials on Growth and Yield of Linseed (Linum usitatissimum L.) - RACHANA HS; SR DODDAGOUDAR; BS GANIGARA; SANGEETA I MACHA; N ANANDA (Seed Research, 2025)
Linseed (Linum usitatissimum L.) is an important oilseed crop, but its small seed size often hampers uniform sowing and seedling establishment. Seed pelleting is an effective technique to enhance seed handling, precision planting, and delivery of beneficial bio-inoculants. A field experiment was conducted to evaluate the effect of different pelleting materials on emergence, growth, yield, and yield attributes of linseed. Eight treatments comprising microbial inoculants (Trichoderma viride, Azospirillum brasilense, Metarhizium anisopliae), organic leaf powders (Pongamia pinnata, Prosopis juliflora, Azadirachta indica), fly ash, and an unpelleted control were tested in a randomized block design with three replications. Seed pelleting significantly improved crop performance compared to the control. Pelleting with Metarhizium anisopliae at a 1:3 ratio recorded the highest field emergence (98.25%), plant height (42.93 cm), number of branches (5.47), capsules per plant (39.94), 1000-seed weight (8.66 g), seed yield per plant (1.83 g), and yield per hectare (894 kg ha- ¹). The unpelleted control showed the lowest values for all parameters. The study concludes that microbial-based pelleting with Metarhizium anisopliae is an effective and eco-friendly strategy to enhance seedling vigour, crop establishment, and productivity of linseed.